2015
DOI: 10.4172/2157-7412.1000261
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cytogenetic Evaluation of Gender in Patients Born with Ambiguous Genitalia from Different Regions of the Valley of Kashmir, North India

Abstract: Ambiguous Genitalia, a rare genetic disorder is caused by defects in the process of fetal sexual determination and differentiation where a newborn needs prompt evaluation to detect lethal conditions and gender assignment. This genetic screening is taken up with an aim to evaluate the prevalence of the patients born with Ambiguous Genitalia existing in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Studies conducted in patients from the valley of Kashmir have reported 58% of genetic females and 42% of genetic males. 16 Many of the previous authors have reported an incidence of more number of genetic females in their study group. 5,12,16 Several authors have also reported the incidence of the mosaic karyotype.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Studies conducted in patients from the valley of Kashmir have reported 58% of genetic females and 42% of genetic males. 16 Many of the previous authors have reported an incidence of more number of genetic females in their study group. 5,12,16 Several authors have also reported the incidence of the mosaic karyotype.…”
Section: Discussionmentioning
confidence: 84%
“…16 Many of the previous authors have reported an incidence of more number of genetic females in their study group. 5,12,16 Several authors have also reported the incidence of the mosaic karyotype. 2,21,22 However, our study failed to detect mosaicism.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations